“The Gospel of John and the role of social memory.” (Theological Kronos, 2019)
The following article, product of personal research in the area of social and collective memory, seeks to take advantage of the contributions of this category in the field of biblical exegesis and hermeneutics. The starting point for this investigation is a text that from the perspective of textual criticism appears as a very late interpolation in the Gospel of John; the perícopa about Jesus and the woman caught in adultery. Should we then discard this story based on textual criticism? Can it have a place in the tradition of the Christian communities of the first centuries and of Jesus himself? These are the concerns that we aim to discuss based on the categoryof social memory in the context of the first Christian communities and their contribution in the development of the written stories we know today as Gospels. What is presented here is a first part of the investigation in which some of the contributions of social memory studies in biblical exegesis are set forth. A further development of the elements is pending a better understanding and application of the text. We hope that this first part of the research will provoke a new look at the biblical text based on the contributions of social memory studies.